Harm's way - Gilstrap, John (Gilstrap, John. Jonathan Grave thriller, 2023)
Henchmen of a vicious drug syndicate have snatched ten missionaries in a remote area of Venezuela and are holding them for ransom. The high-priority rescue op comes as a personal plea from FBI Director Irene Rivers, who has a very special interest in one of the hostages. The mission is strictly off the books, and there can be no international incident. With his key operatives Gunslinger and Boxers, Jonathan Grave infiltrates the enemy camp. Right away, the rescue mission morphs into something far more dangerous, not just to Jonathan and his team, but to the whole world.